The Effect of Intellectual Capital on Stock Return Through Financial Performance - Nadia Berliana Safitri; Riska Nisrina; Adisti Wulan Suci; Mada Purwanto Wahyu Nugroho (PT. Publikasiku Academic Solution, 2024)
In the era of globalization and increasingly fierce competition, companies are required to increase their competitiveness by optimally utilizing the assets they own, one of the assets that is increasingly important for companies is intellectual capital. The purpose of this study is to examine whether intellectual capital affects stock returns through financial performance, which has the aim of knowing the influence of intellectual capital on financial performance, the influence of intellectual capital on stock returns, the effect of stock returns on financial performance, and whether or not financial performance mediates the relationship between intellectual capital and stock returns. A multiple linear regression analysis model with path analysis is an analysis method used in this study that aims to test whether there is a direct or indirect influence between independent, dependent, and intervening variables. Data testing tool using SPPS24 software. The population object in this study is companies listed on the IDX Indexes LQ45 for the 2018-2022 period; with the purposive sampling method, the samples collected are 33 companies with a total of 45 companies' observation data. The results showed that intellectual capital affects financial performance. These results show that the effect of financial performance on stock returns is statistically significant. The indirect influence of the statistical analysis results is greater than the direct influence of intellectual capital on stock returns. Thus, financial performance mediates the influence of intellectual capital on stock returns. This result explains that the company must utilize and maintain intellectual capital, and sound financial performance affects the stock returns received by investors, which later show good company value. Companies must utilize and maintain their intellectual capital because good financial performance, which results from the utilization of intellectual capital, will increase stock returns and reflect good company value in the eyes of investors.